Mining expansion may reduce livestock but facilitate vicuñas recovery in tropical Puna of South America - Sandoval-Calderon, Ana Patricia; van Kuijk, Marijke; Hautier, Yann; Alberto, Humber; Verweij, Pita A. (Frontiers in Conservation Science, 2024)
High-elevation tropical grasslands in South America are vital for sustaining the livelihoods of indigenous communities, particularly in the Central Andes where herding of both wild and domesticated camelids has been a primary socio-economic activity for centuries. However, these grasslands are facing challenges due to changes in land use, economic activities, and climate, posing threats to the sustainability of camelid herding. Here, we determine the intricate relationship between land use management and camelid populations of the highlands of Apolobamba National Park in Bolivia. We identified two critical milestones in land use management across the indigenous communities: the creation of the Tierra Comunitaria de Origen (TCO) in 1999 and the expansion of the National Park in 2000. These initiatives collectively resulted in the diversification of livelihood sources by increasing the number of mining concessions and facilitating the management of wild camelids for their wool and fibers, catering to international markets. We found that this diversification of livelihood sources was negatively related to the densities of domesticated camelids across the studied communities. In contrast, the densities of wild camelids populations increased with an increasing number of mining concessions, likely due to local conservation efforts and reduced competition with livestock. Our results indicate a potential shift in land use management strategies and suggest that mining activities encroach upon pastoralism practices within indigenous communities. Understanding the long-term effects of land use changes is essential for providing comprehensive and sustainable land use strategies that will support both grasslands and animal conservation while providing livelihood security in this ecologically sensitive region.